2nd Annual ASCOPE Laboratory Test Correlation Programme on CFR Engine (1981) - Bustami Mustafa; E. Jasjfi (Testing Center for Oil and Gas LEMIGAS, 1982)
ASCOPE Work Programme for 1981 directed the Technical Committee to conduct the 2nd Annual Laboratory Test Correlation Programme for CFR Engines among petroleum laboratories in the ASCOPE member countries. Member countries taking part in this correlation programme are Indonesia with seven laboratories participating, Malaysia with two laboratories, Thailand and the Philippines with two laboratories each. LEMIGAS Laboratory of Indonesia, as coordinator in this correlation programme, provided the samples to be sent to each participating laboratory. After being tested by the participating laboratories, the test results on these samples were to be sent to PPTMGB